Kedudukan Pelaku Usaha dan Konsumen dalam Hukum Perlindungan Konsumen (Produk Mi Soun Mengandung Klorin) - Heru Saputra Lumban Gaol; Fransisca Yanita Prawitasari (Fakultas Hukum Universitas Surabaya, 2018)
Food is one of the primary needs of humans. In terms of producing food, it cannot be completely separated from the use of Food Additives. Article 1 paragraph (1) of Law Number 33 Year 2012 concerning Food Additives determine Food Additives are ingredients added to food to affect the nature or form of food. This indicates that Food Additives may affect the quality of the product. In practice, not all Food Additives are used by sellers safe for consumers' health. In fact, Article 4 letter a of Law Number 8 of 1999 concerning Consumer Law determines that consumers have the right to conveniences, security and safety in consuming goods and/or services. This is also in line with the seller's obligations that specified in Article 7 of the Consumer Law. A several cases of chlorine additives on mi soun at Klaten, Jember, and Jambi show a lack of awareness of sellers and consumers in recognizing which food additives are harmful for health. Consumer law as a progressive law strives to be a legal means that establish consumer awareness and sellers awareness in order to realize their rights and obligations. Progressive consumer law also indicates a balance between sellers and consumers in harmonizing the principles of caveat venditor and caveat emptor.